JURIDICAL ANALYSIS OF THE TRANSFORMATION OF PEOPLE’S CREDIT BANKS INTO PEOPLE’S ECONOMIC BANK REVIEWED FROM LAW OF THE REPUBLIC OF INDONESIA NUMBER 4 YEAR 2023 ON THE DEVELOPMENT AND STRENGTHENING OF THE FINANCIAL SECTOR - Keylia Sayidina Islam; Paramita Prananingtyas; Rahandy Rizki Prananda (Diponegoro Law Journal, 2025)
People’s Economic Bank is a financial institution that operates conventionally or based on Sharia Principles and does not directly provide services in payment traffic. This study focuses on the legal analysis of the transformation of People’s Credit Bank into People’s Economic Bank, particularly examining the legal background and legal implications for debtors, creditors, and regulators. Using a qualitative content analysis method and literature-based data, the research finds that this transformation is a comprehensive institutional restructuring mandated by the Financial Sector Development and Strengthening Law. The transformation expands business activities and access to capital, allowing People’s Economic Banks to grow within a more open, competitive, and inclusive financial ecosystem. Legal consequences vary depending on each party’s legal relationship with the bank. However, the People’s Economic Bank, as a transformed entity, must proactively deliver information and education to prevent public misperceptions regarding the legal effects of this institutional change